Outcome Measures for Disease Monitoring in Intraocular Inflammatory and Infectious Diseases (OCTOMERIA): Understanding the Choroid in Uveitis with Optical Coherence Tomography (OCT). (7th February 2023) - Agrawal, Rupesh; Weng, Rei Chern; Fonollosa, Alex; Giralt, Lena; Artaraz, Joseba; Yang, Peizeng; Huang, Fanfan; Tan, Bingyao; Schmetterer, Leopold; Sen, Alok; Gupta, Vishali; Xin, Wei
ABSTRACT: Purpose: To compare imaging modalities for the choroid of the eye, and evaluate various choroidal changes in uveitides entities. Methods: A comprehensive systematic literature review was conducted looking at current imaging modalities available to assess choroid architecture and commonly used parameters available to qualify and quantify choroidal changes, before looking at specific uveitides entities with choroidal involvement which have been broadly separated into non-infectious and infectious in etiology. Results: We describe the various modalities currently available to evaluate the choroid of the eye such as Ultrasound B Scan, ICGA, and OCT. Choroidal changes in various ocular and systemic diseases such as Behcet's Disease, Sarcoidosis, Syphillis, Tuberculosis, and many more have been reported and published. Conclusion: Multiple choroidal tomographic and angiotomographic findings have been demonstrated for evaluation in uveitis. These findings can manifest in multiple ocular and systemic diseases, and can be illustrated using the various imaging modalities at present. Future advancements in choroidal imaging would help to adapt these findings into parameters for clinical practice to properly evaluate these ocular and systemic diseases.